Dynamic Modelling and Control Design of Advanced Photovoltaic Solar System for Distributed Generation Applications - Molina, Marcelo Gustavo (2010)
Presently, grid-connected photovoltaic (PV) solar systems are becoming the most important application of PV systems. This trend is being increased because of the many benefits of using renewable energy sources (RES) in modern distributed (or dispersed) generation (DG) systems. This electrical grid structure imposes on the distributed generator new requirements of high quality electric power, flexibility, efficiency and reliability. This paper proposes a novel high performance power conditioning system (PCS) of a three-phase grid-connected PV system and its control scheme for applications in DG systems. The PCS utilizes a two-stage energy conversion system topology composed of a DC/DC boost converter and a diode-clamped three-level voltage source inverter (VSI) that satisfies all the stated requirements. The model of the proposed PV array uses theoretical and empirical equations together with data provided by manufacturer of PV panels, solar radiation and cell temperature among others variables, in order to accurately predict the current-voltage curve. Moreover, based on the state-space averaging method a new three-level control scheme is designed, comprising a full decoupled current control strategy in the synchronous-rotating d-q frame, capable of simultaneously and independently exchanging both active and reactive powers with the distribution system. Validation of models and control algorithms is carried out through digital simulations using the MATLAB/Simulink environment and implementing a 250 Wp PV experimental set-up.